Power asymmetry and escalation in bargaining - Ulrike Vollstädt (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
Bargaining is prevalent in economic interactions. Under complete information, game theory predicts efficient bargaining outcomes (immediate acceptance of first offer) (see Rubinstein, 1982). However, continuous rejections of offers leading to inefficient delays (escalation) have regularly been found in previous bargaining experiments even under complete information (see Roth, 1995). I test experimentally (1) whether power asymmetry leads to more escalation in bargaining and (2) whether perspective-taking reduces escalation. I find that power asymmetry increases escalation, but that perspective-taking does not reduce escalation.
Keywords: C78; D89; 330; two-person bargaining experiment; asymmetric power; escalation; perspective-taking; Verhandlungstheorie; Macht; Test